2019
DOI: 10.3389/fmicb.2019.01930
|View full text |Cite
|
Sign up to set email alerts
|

Cas9 Contributes to Group B Streptococcal Colonization and Disease

Abstract: Group B Streptococcus (GBS) is a major opportunistic pathogen in certain adult populations, including pregnant women, and remains a leading etiologic agent of newborn disease. During pregnancy, GBS asymptomatically colonizes the vaginal tract of 20–30% of healthy women, but can be transmitted to the neonate in utero or during birth resulting in neonatal pneumonia, sepsis, meningitis, and subsequently 10–15% mortality regardless of antibiotic treatment. While variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(75 citation statements)
references
References 109 publications
3
72
0
Order By: Relevance
“…To mimic the human blood-brain barrier (BBB), the human cerebral microvascular endothelial cell line hCMEC/D3 was utilized. The in vitro assays for adhesion and invasion were performed using pre-established protocols (37,38). To control for the presence of the plasmid backbone in the complement strain, COH1(pABG5), COH1Δ mprF (pABG5), and COH1Δ mprF (pGBSMprF) strains were used.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To mimic the human blood-brain barrier (BBB), the human cerebral microvascular endothelial cell line hCMEC/D3 was utilized. The in vitro assays for adhesion and invasion were performed using pre-established protocols (37,38). To control for the presence of the plasmid backbone in the complement strain, COH1(pABG5), COH1Δ mprF (pABG5), and COH1Δ mprF (pGBSMprF) strains were used.…”
Section: Resultsmentioning
confidence: 99%
“…Assays to determine the total number of bacteria adhered to host cells or intracellular bacteria were performed as described previously (37,38). Briefly, bacteria were grown to mid log phase (OD 600nm 0.4-0.5) and normalized to 1 × 10 8 to infect cell monolayers at a multiplicity of infection (MOI) of 1 (1 × 10 5 CFU per well).…”
Section: Methodsmentioning
confidence: 99%
“…CRISPR-Cas systems modulate bacterial-host interactions, the mechanisms of which are currently evolving. Relative to the wild-type, Neisseria , Streptococcus , and Campylobacter △ cas9 strains adhere poorly to mammalian host cells ( Ma et al., 2018 ; Shabbir et al., 2018 ; Heidrich et al., 2019 ; Spencer et al., 2019 ; Gao et al., 2019 ). The S. pyogenes mechanism involves Cas9-mediated down-regulation of the FasA/FasB TCS that downregulates adhesion factors ( Gao et al., 2019 ).…”
Section: Physiological Roles Of Crispr-cas Observed In Bacteriamentioning
confidence: 99%
“…These studies suggest complex interdependence of CRISPR and DNA repair systems, the mechanisms of which are still elusive. Transcriptomic and proteomic studies of △ cas9 S. pyogenes (type II-A) ( Gao et al., 2019 ), Group B Streptococcus (type II-A) ( Spencer et al., 2019 ), and Riemerella anatipestifer (type II-C) ( Wang et al., 2019 ) have indicated both up- and down- regulation of several endogenous genes, the implications of which are not clear. Several studies in Myxococcus xanthus have shown that CRISPR systems are involved in cell-stress dependent sporulation (type I-C) and fruiting body development (type III-B) ( Viswanathan et al., 2007 ; Wallace et al., 2014 ).…”
Section: Physiological Roles Of Crispr-cas Observed In Bacteriamentioning
confidence: 99%
“…Together with improved computational tools for data analysis, innovations in RNA-seq technologies are contributing to a better understanding of RNA biology and intermolecular interactions that govern RNA function, as well as transcriptional dynamics changes driving bacterial response and adaptation, to distinct growth conditions and external stimuli [9]. Recently, RNA-seq technology has been successfully applied to clarify some molecular mechanisms of pathogenesis in S. agalactiae [8,[10][11][12][13][14][15]. The first S. agalactiae comparative transcriptomic study evidenced several genetic factors (in particular related to lactose metabolism) likely important in adaptation to the bovine environment [10].…”
Section: Introductionmentioning
confidence: 99%